Інкрустація ячменю озимого препаратами Антистрес та Марс ELBi - Ярчук, Ігор Іванович; Yarchuk, Igor; Божко, В. Ю.; Bozhko, V.; Позняк, Василь Васильович; Poznyak, Basil; Кравченко, К. О. (Дніпровський державний аграрно-економічний університет, 2015)
Досліджено вплив препаратів рістрегулюючої та кріопротекторної дії на виживаність та урожайність рослин ячменю озимого сорту Основа в умовах північного Степу. Встановлено позитивний вплив інкрустації насіння препаратом Антистрес на перезимівлю рослин ячменю. Використання Марс ELBi на посівах ячменю озимого в осінній період не ефективне. Barley is one of main cultures not only inUkrainebut in the whole world. Barley has very high productivity especially winter barley. But the main disadvantage which keeps it under increasing of planting acreages is its low cold resistance.The main task for us was to investigate possible increasing of winter barley cold resistance using agents Antistress and Mars ELBi. These agents were used with semi-dry treatment of Osnova grain.Mars ELBi is a complex agent which combines characteristics of agent Mars-EL and natural bishofite. It prevents from formation of ice crystals, decreases speed of water flow, increases osmotic pressure and increases resistance of plants. Agent Antistress can improve plant capability to extremal weather conditions. This capacity is a result of implication of physiologically active substances. The agent contains Mars-EL, dimethyl sulfoxide, glycerin, phosphorus (P2O5 ≥ 50 %), potassium (K2O ≥ 34 %), humic acids. Sprinkling of vegetative plants with dimethyl sulfoxide and sucrose was set as a standard.Experiments approved positive effect of incrustation with Antistress on cold resistance of winter barley in conditions of Northern Steppe. Productivity increases on 0,2 tons per ha when compared to control and figures up to 3,9 tons per ha. Treatment with Mars ELBi enhances plant growth in autumn, but it has a bad influence on cold resistance.
Incrustation of winter barley with agents Antistress and Mars ELBi
Keywords: ячмінь озимий; winter barley; регулятор росту; plant growth regulators; кріопротектор; cryoprotective agent; інкрустація; incrustation; виживаність; survivance; урожайність; productivity